The Investigation of Antifungal Activity and Durability of Natural Silk Fabrics Dyed with Madder and Gallnut - (:unkn) unknown (TAYLOR & FRANCIS INC, 2017)
In this study, five silk fabrics were separately dyed withmadder (Rubia tinctorium L.) and gallnut (Quercus infectoria Olivier) in different percentages and then tested for antifungal activity against Candida albicans DSMZ 1386. The one having highest antifungal activity was washed 5 times under same conditions and samples were taken after every wash. They retained nearly 99.98 % activity up to five launderings against Candida albicans. In addition, coloring compounds and their peak heights in dyed silk fabrics were detected by high performance liquid chromatography with diode array detection (HPLC-PDA). Color values of the dyed silk fabrics were measured by CIEL*a*b* spectrophotometer.
Keywords: Antifungal activity; color measurement; durability; HPLC-PDA; natural dyeing; natural silk; RUBIA-TINCTORUM; WALLOON OAK; HPLC; TEXTILES; L.